Personal factors related to self-care management among people with hypertension at primary health care: A cross-sectional study - Anggraini Dwi Kurnia; Sri Hariyati; Nur Melizza; Chairul Huda Al Husna; Anchaleeporn Amatayakul; Adelia Handoko (Jurnal Keperawatan Padjadjaran, 2023)
Background: Hypertension requires long-term treatment and can last a lifetime. Recommendations for hypertensive patients, where it is necessary to change behavior related to self-care, consist of increasing a healthy diet, limiting sodium intake, increasing physical activity, reducing smoking, and reducing alcohol consumption. Objective: The purpose of this study was to identify the self-care model of patients with hypertension in primary healthcare in Kota Malang. Methods: This study's design was descriptive analytic with a cross-sectional methodology. Using G Power, 321 hypertension patients were used as samples. Purposive sampling was used in this study. The instruments used H-SCALE, also known as the Hypertension Self-Care Activity Level Effects. Pearson Chi-squared test was used to examine correlations among variables. Results: Factors of gender (p=0.001) and education (p=0.020) are related to self-care in hypertensive patients. Majority of respondents were women, 223 people (69.5%), Most of the respondents had elementary school education, 136 people (41.4%), the majority of the 321 respondents (216, 67.3%) have moderate self-care category. Gender and age were significant factors associated with self-care among hypertensive patients (p<0.05)  Conclusion: Gender and education level have significant correlation with self-care management of hypertension. Providing self-management intervention by considering gender and education level needs improvement. Other factors need to be explored in  further research.